Clinical Relevance of Estrogen Reactivity in the Breast Cancer Microenvironment - Takeshita, Takashi; Tokumaru, Yoshihisa; Oshi, Masanori; Wu, Rongrong; Patel, Ankit; Tian, Wanqing; Hatanaka, Yutaka; Hatanaka, Kanako C.; Yan, Li; Takabe, Kazuaki (Frontiers in Oncology, 2022)
Purpose Estrogen signals play an important role in the phenotype of estrogen receptor-positive breast cancer. However, comprehensive analyses of the effect of responsiveness to estrogen signals on the tumor microenvironment and survival in large cohorts of primary breast cancer patients have been lacking. We aimed to test the hypothesis that estrogen reactivity affects gene expression and immune cell infiltration profiles in the tumor microenvironment and survival. Methods A total of 3,098 breast cancer cases were analyzed: 1,904 from the Molecular Taxonomy of Breast Cancer (METABRIC) cohort, 1,082 from The Cancer Genome Atlas (TCGA) cohort, and 112 from the Hokkaido University Hospital cohort. We divided the group into estrogen reactivity-high and estrogen reactivity-low groups utilizing the scores of ESTROGEN_RESPONSE_EARLY and ESTROGEN_RESPONSE_LATE in Gene Set Variation Analysis. Results Breast cancer with high estrogen reactivity was related to Myc targets, metabolism-related signaling, cell stress response, TGF-beta signaling, androgen response, and MTORC1 signaling gene sets in the tumor microenvironment. Low estrogen reactivity was related to immune-related proteins, IL2-STAT5 signaling, IL6-JAK-STAT3 signaling, KRAS signaling, cell cycle-related gene sets, and EMT. In addition, breast cancer with high levels of estrogen reactivity had low immune cytolytic activity and low levels of immunostimulatory cells. It also had low levels of stimulatory and inhibitory factors of the cancer immunity cycle. Patients with high estrogen reactivity were also associated with a better prognosis. Conclusion We demonstrated the relationship between estrogen reactivity and the profiles of immune cells and gene expression, as well as survival.